Isolation and Identification of Fungal Isolates caused Otomycosis from some Hospitals and Clinics in Mosul with Determination of Their Virulence Factors - Al-Sharrad, Nabeel; Muhammad A. Al-Kataan; Maha A. Al-Rejaboo (Al-Qadisiyah Journal of Pure Science, 2021)
Otomycosis is a fungal infection that frequently involves the external auditory canal. In this study, we aimed to isolation and identification the fungal isolates as etiological agents of otomycosis from some hospitals and clinics in Mosul with determination of their virulence factors of fungal etiological agents. Positive fungal infection was found in (43) samples (71.6%). The most common fungal pathogens were Candida and Aspergillus species, with Candida parapsilosis being the predominant isolates in (11) samples (16.6%). Otomycosis was more common in Female in (26) samples (43.3%).Otomycosis was the highest prevalence aged group 15-40 years (19) samples (31.3%). The present study of virulence factors revealed that the highest biofilm formation isolates were C. parapsilosis is (10) isolates which were distributed between (2) strong and (8) weak biofilm formation.Where C.trpicales, was recorded as least isolates for biofilm production.